Redes de solidariedade e afeto : trajetória do programa Pró-Equidade de Gênero e Raça (2005-2023) - Dias, Erica da Cruz Novaes Gonçalves, 1983- (2024)
Orientadores Leda Maria Caira Gitahy, Carla Ladeira Pimentel Águas